Interference Between Indonesian and Arabic: Kalam and Tarjamah Approach - Khopipah Rohmatillah; Zakia Jauharotul Munfarida; Muhamad Maulana Yusup (Gunung Djati Conference Series, 2026)
This research aims to analyze the interference between Arabic and Indonesian languages in speech and translation. Interference is defined as the influence of the source language (Arabic) on the target language (Indonesian) in the translation process. This research uses a qualitative method with text analysis and interview techniques. Research data was obtained from the results of online interviews and analysis of translation texts. Based on the research conducted, it shows that there is language interference between Arabic and Indonesian languages in Speech and Translation at the phonological, morphological, syntactic, and semantic levels. This interference is caused by several factors, namely the dominance of the mother tongue (Indonesian), lack of mastery of Arabic, and the habit of using Indonesian language structures in Arabic. Finally, this interference has an impact on the quality of speech and translation, so it is necessary to find solutions. Solutions that can be done include improving Arabic language proficiency, for example by maturing the mastery of the 4 skills (Istima', kalam, qiro'ah, and kitabah), training translation skills, and using appropriate dictionaries and references.